Root cause analysis of tubing and casing failures in low-temperature carbon dioxide injection well. (October 2019) - Chen, Shengshan; Wang, Hanxiang; Liu, Yanxin; Lan, Wenjian; Lv, Xiaoxiao; Sun, Bingyu; Yuan, Dexin
Abstract: As a tertiary oil recovery technology, CO2 injection is a promising method to rejuvenate the oil reservoirs after the primary production. However, with the injection of low-temperature liquid CO2 into deep geological structures for the purpose of CO2 storage and/or enhanced oil recovery (CO2 -EOR), some of the injection wells experienced problems with tubing and casing failures. The objective of this paper is to find the root cause of tubing and casing failures. The thermo-mechanical coupling numerical simulation model and laboratory experiments are conducted to investigate the effect of frost heaving on tubing and casing. The simulation results well agree with those experimental data, which implies the numerical model is valid and can describe the thermo-mechanical process in the CO2 injection well. Then, the effect of tubing coupling, annulus width, thickness and operation pressure are explained and analyzed by combining the production parameters and numerical simulation. The results indicate that: (a) The frost heaving generated by volume expansion with freezing of annulus liquid during the low-temperature CO2 injection is the root cause of tubing and casing failures. (b) The decrease of annulus width and increase of thickness will lead to a dramatically decrease of tubing and casing stress. (c) Increase tubing pressure can help to reduce the tubing stress. Finally, based on the failure mechanism and frost heaving characteristics, an optimal tubing-casing combination is proposed to prolong the operation life of tubing and casing. Highlights: Frost heaving pressure is the root cause of tubing and casing failures. Effect of different structural and operational parameters on frost heaving characteristic are analyzed. Decreasing annulus width, increasing tubing thickness and pressure are effective measures to reduce frost heaving effects. An optimal tubing-casing combination is obtained.